Modelling the interactive influence of intellectual capital indicators - Anderson, Henry Junior; Stejskal, Jan (Academic Conferences and Publishing International, 2019)
Knowledge generation, in contemporary times, has dictated the economic strength and national and regional competitive advantage. The advent of the open innovation model has driven firms to collaborate and engage in external interactions to incite their innovation spark to become even more competitive globally and nationally. There have been a wealth of success in creating intellectual capital in the European Union. In line with that, subsequent funding have been provided for small and medium sized firms (SMEs) with the view of assisting them to individually or cooperatively generate intellectual capital. However, even as human resources, cooperation and other environmental factors have been acclaimed to influence regional intellectual capital capacity, we question whether these factors offer an interactively significant influence on themselves in creating intellectual capital. This will enable identification of catalytic indicators to expertly position regional activities that generate regional competitive advantage. Using the Structural equation modelling (SEM) and data from European Innovation Survey (2018), research aims to test the interactive influence of the selected indicators of intellectual capital and their significance in generation intellectual capital represented by patents, trademarks and design applications. The results revealed that whilst research system attractiveness and firm-to-firm or academia linkages were very significant in generating intellectual capital, human capital were not significant in generating intellectual capital contrary to mass of literature. Attractiveness of research systems were strongly significant in affecting the human resource structure and innovation friendliness of member states and generation of intellectual capital. Private, public and venture capital were found to have been strongly influenced by labour structure and friendliness of a geography whilst it also strongly affected the cooperation tendencies of firms and academia. Policies that aligned regional strengths to these findings were further recommended. © 2019 Academic Conferences Limited. All rights reserved.
Modelování interaktivního vlivu ukazatelů intelektuálního kapitálu
Keywords: Cooperation, Human capital, Innovation, Intellectual capital, Public and private funds; Spolupráce, lidský kapitál, inovace, intelektuální kapitál, veřejné a soukromé fondy